oceanic tauromachy - Mukherjee, Subham (UnderCurrents: Journal of Critical Environmental Studies, 2025)
oceanic tauromachy conceives of the new ocean beyond the tropes of catastrophe and disaster, as an evocative ‘zone’ of evolution, transformation, and unforgiving change, beyond the ontology of despair. The ecological turn has transformed the oceans into complex zones. It has become an apophenic abstraction stitching together other abstractions—an abcanny zone of aberrating non-meaningfulness, of clandestine unbeing, of fractal unbecoming. oceanic tauromachy is musica universalis of residual divinity in toxicity, of lingering sanctity in erosion. Here I invoke the froth that has been gurgling out of the spasms of the sea. The new ocean has become a breeding haven for chthonic deception which has been accommodating the holy havoc of bioprospecting exploitation. The sea bed exhibits the paralysis of our unhinged telos. The ocean has lost its topos. oceanic tauromachy is a will to recover; a preamble to invite and engage a diagnostic planetarity in praxis.